Pharmacokinetics of mometasone furoate delivered via two dry powder inhalers. (October 2021) - Vaidya, Soniya; Ziegler, Dominik; Tanase, Ana-Maria; Malmqvist, Ulf; Kanniess, Frank; Hederer, Bettina; Hosoe, Motoi
Abstract: Background: QMF149 is an inhaled fixed-dose combination of indacaterol acetate and mometasone furoate (MF) delivered via Breezhaler®, under development for once-daily treatment of asthma. MF delivered via Twisthaler® is approved as Asmanex® Twisthaler® for the treatment of asthma. Bridging of MF delivered via Twisthaler® to MF delivered via Breezhaler® was undertaken as part of QMF149 development to enable dose comparisons between the devices. Pharmacokinetics (PK) of MF were characterized in two studies; a single dose PK study in healthy volunteers and a pharmacokinetic/pharmacodynamic (PK/PD) study in asthma patients. Objectives: The PK study in healthy volunteers evaluated the PK of single doses of MF via Breezhaler® (50–400 μg) and compared systemic exposure of MF following administration via Breezhaler® and Twisthaler® 400 μg (2 inhalations of 200 μg). The study in patients with asthma characterized the MF PK profile following once-daily inhalation of MF via Breezhaler® and Twisthaler® devices for 4 weeks. Methods: In the open-label, single-dose, crossover study, healthy subjects sequentially received MF via Twisthaler® (400 μg, medium-dose inhaled corticosteroid [ICS]) and escalating doses via Breezhaler® (50, 100, 200, 400 μg). PK data were obtained up to 72 h post-dose. In the double-blind, double-dummy, parallel-group study, asthma patients were randomised to receive either MF 80 μg (low-dose ICS) or 320 μg (high-dose ICS) via Breezhaler®, or 200 μg (low-dose ICS) or 800 μg (2 inhalations of 400 μg; high-dose ICS) via Twisthaler® once daily for 4 weeks. PK sampling was performed on Days 1 and 28 at pre-dose and up to 24 h post-dose. Results: In the healthy volunteer PK study, 20 healthy subjects completed all treatments. Dose-normalised AUClast of MF was 1.8–1.9-fold higher when delivered via Breezhaler® versus Twisthaler®. AUC and Cmax of MF increased in a dose-proportional manner over the range of 50–400 μg via Breezhaler®. Results from this study guided dose selection of MF via Breezhaler® for the asthma study. In the asthma study, in a subset of 96 patients, mean systemic exposure (AUClast and Cmax ) for MF 80 and 320 μg via Breezhaler® was comparable with MF 200 and 800 μg via Twisthaler®, respectively, on Day 28. Conclusion: PK characterization in a healthy volunteer PK study and subsequently an asthma study enabled selection of 80 μg (low), 160 μg (medium), and 320 μg (high) delivered via Breezhaler® as MF doses comparable to the 200 μg, 400 μg and 800 μg doses delivered by Twisthaler®, respectively, as part of QMF149 formulation development.